FAO publications titles in print - Food and Agriculture Organization of the United Nations (Rome, Italy : Food and Agriculture Organization of the United Nat ions, 2005)
This Catalogue presents all FAO titles currently available for sale in English, French and Spanish, published by or co-published with FAO. It includes books, periodicals, CD-ROMs and on-line data.
CD-ROM.
Keywords: Food and Agriculture Organization of the United Nations -- Catalogs; Agriculture -- Bibliography -- Catalogs; Nutrition -- Bibliography -- Catalogs